Evaluating evidence : a positivist approach to reading sources on modern Japan - Akita, George (University of Hawai'i Press, 2008)
George Akita persisted in the difficult task of reading documentary sources in Japanese, out of the conviction of their centrality to the historian's craft and his commitment to a positivist methodology to research and scholarship. In this book, he explains what he means by a positivist approach to reading sources.